The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência